ORGANIZATIONAL READINESS FOR SAP S/4HANA MIGRATION IN MINING ASSET MANAGEMENT - Rr. Aria Prita Ekaristi; Mokhamad Suef (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2026)
Digital transformation in asset-intensive industries increasingly depends on the successful migration of legacy Enterprise Resource Planning (ERP) systems toward integrated digital platforms such as SAP S/4HANA. However, despite substantial technological investment, ERP transformation projects continue to experience high failure rates due to organizational resistance and inadequate change readiness. This study investigates organizational readiness for SAP ECC to S/4HANA migration within the Operations Maintenance division of an Indonesian mining company managing more than 20,000 operational assets. Using a qualitative single-case study design, this research integrates the ADKAR model and Critical Success Factors (CSF) framework to examine both individual readiness and organizational enablers of digital transformation. Data were collected during the pre-implementation phase through in-depth interviews, focus group discussions, participatory observation, and document analysis involving 14 informants across strategic, tactical, and operational levels. The findings reveal that awareness of technological urgency was relatively strong, driven by SAP ECC obsolescence and operational modernization pressures. However, gaps emerged in the dimensions of desire, ability, and reinforcement, particularly among operational users facing process complexity and adaptation challenges. The study further identifies leadership commitment, communication quality, user involvement, and role-based training as dominant organizational enablers influencing readiness outcomes. This research contributes theoretically by integrating micro-level and macro-level change perspectives and practically by proposing a change management roadmap for large-scale ERP migration in mining organizations